LEGAL REGULATION OF CONFESSIONAL RELATIONS IN THE REPUBLIC OF KAZAKHSTAN - Toylybekova, Эльмира Орынтаевна; Мадина Қойшыбайқызы; Shukenova , Жадыра Сламхановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
Relations between the state and religious organizations in human history play a significant role. Since religion and law are powerful regulators of human behavior, and religious organizations and the state are forms of such behavior. In modern society, there are many religious organizations that are one of the main elements of the social structure of such a society.